Analisis Struktur Modal, Ukuran Perusahaan, Profitabilitas, Terhadap Nilai Perusahaan - Nuryana, Hilmy; Norisanti, Nor; Nurmala, Resa (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study is to determine the effect of Capital Structure, Company Size, and Profitability on Company Value in the company for the period 2015 quarter I – 2022 quarter IV. The population in this study is the financial statements of PT. Tri Banyan Tirta Tbk. The object of this study is Capital Structure (X1), Company Size (X2), Profitability (X3), and Company Value (Y). The research method used is descriptive and associative with a quantitative approach. The data analysis techniques used in this study are statistical and descriptive, which use a number of tests such as classical assumption tests consisting of normality tests, multiple linear regression analysis, multiple correlation coefficients, determination coefficients, hypothesis tests (t tests) using SPSS applications and horizontal analysis. The results showed that from the t-test (partial) Capital Structure partially showed results of 2.101 where t-count was 2.101> t-table 2.042 with a significance value of 2.101, Next, Company Size shows the t-count <t-table (0.472<2.042) with a significance value of 0.640, next for Profitability it shows the t-count <t-table (2.156>2.042) with a significance value of 0.040. The conclusion is that Capital Structure partially has a positive and significant influence on Company Value, while Company Size has a negative and insignificant influence on Company Value then Profitability has a positive and significant influence on Company Value.